upp-based counterselective genetic cloning to create rotavirus vaccine constructs using Lactobacillus acidophilus platform - Kiehl, Paris, author; Kiehl, Sophie M., author; Swartzwelter, Benjamin J., author; Vilander, Allison, committee member; Kinkel, Traci, committee member; Fletcher, McKenzie, author; Dean, Gregg, advisor (Colorado State University. Libraries, 2025)
Rotavirus is a major public health burden that causes severe gastroenteritis and kills more than 200,000 infants per year. Live attenuated vaccines have reduced effectiveness in low- and middle-income countries, which is correlated to gut microbiota composition. To combat this, we are developing an orally administered vaccine using the probiotic Lactobacillus acidophilus as a vector. Here, we used upp-based genetic cloning to create multiple strains of L. acidophilus that express rotavirus' VP7 glycoprotein behind the highly expressed metabolic enzyme enolase. This counterselective genetic cloning process uses a temperature-sensitive helper plasmid and recombination-directing vector plasmid to integrate target sequences into the bacterial genome and remove selectable markers. Vaccine constructs were evaluated for recombination using genetic analysis and immunoassays. The vaccines are being tested in murine and porcine models to evaluate their ability to protect hosts against rotavirus.
Microbiology, Immunology, & Pathology
Additional authors supplied by Paris Kiehl.
Keywords: probiotic-based vaccine; rotavirus; genetic cloning